A dynamic model for crime control and policy evaluation. Issue 6 (1999) - Ahmed Ahmed, N. U. N. U.; Rahim Rahim, M. A. M. A.
Abstract : The paper is concerned with the development of a rigorous mathematical model describing the dynamics of criminal population subject to sentencing policies of any penal (legal) system. The model enables evaluation of the impact of preventive measures used in the society and correctional measures used by the penitentiaries. A performance index reflecting the effectiveness of such measures and the cost to the society for providing the same is introduced and the question of optimality discussed.